The Influence of Financial Attitude and Financial Knowledge on Financial Management Behavior Moderated by Locus of Control in Generation Z - Sangari Andrew Griffin; Novie P. Sibilang (PT FORMOSA CENDEKIA GLOBAL, 2022)
In accelerating the economy, especially in the field of finance, Generation Z is easily influenced by developments that have an impact on behavior. This study aims to analyze the effect of financial attitude and financial knowledge on financial management behavior, with locus of control (Internal and External) partially as a moderating variable in generation Z. Using 210 observations and an analytical method using multiple regression, this study found that financial Attitude is proven to have a positive and significant effect on financial management behavior and external locus of control is able to moderate financial knowledge on financial management behavior because the external locus of control dominates the behavior of generation Z. The implications of this research are expecting the education system to pay more attention to the behavior of generation Z in relation to cognitive development. children are more specific on financial literacy in forming a positive attitude towards financial arrangements